School related factors affecting non communicable diseases risk factors among 13-15 years old adolescents from two schools in Delhi - Kedar, Ashwini; Gupta, Sanjay (International Journal Of Community Medicine And Public Health, 2019)
Background: Children and adolescents are more vulnerable to developing NCD (non communicable diseases) risk factors due to changing lifestyles. Hence it is essential to recognize NCD risk factors among adolescents. School plays an important role in imparting knowledge and shaping the behaviours and practices among children. This study focusses on the school related factors that may be influencing the NCD risk factors among adolescents. Methods: The study was conducted among 438 students, 13 to 15 years old of two central government schools in Delhi. A self-administered modified STEPS questionnaire, an observation checklist for assessing facilities at schools and an interview schedule for school staff were used to collect data. Results: The statistically significant determinants of inadequate fruits and vegetable intake and excess fast food intake were consumption of fast food from vendors selling food outside the school (OR=4.36), inadequate physical activity at school (OR=2.56) and feeling stressed at school (OR=2.93). Physical activity at school was an important determinant for overall physical activity of students (OR=2.38). Current tobacco use and current alcohol use was determined by feeling stressed at school (OR=3.12). Health education classes at school had a protective effect on the NCD risk factors. Conclusions: Many school related factors such as absence of playground at school, stressed life at school and vendors selling fast food outside school were seen to influence lifestyle risk factors amongst adolescents. Hence an active involvement of school by increasing health education classes and providing adequate facilities for physical activities may help in reducing the NCD risk factors among students.